Reactionary - electrodiffusion equations of transport processes of electrolyte solutions of radioelements through porous clayey structures - Tokarchuk, M.V.; Hlushak, P.A.; Krip, I.M.; Shymchuk, T.V. (Condensed Matter Physics, 2007)
The statistical model of the water solution of radioactive elements and the porous clayey matrix is proposed. The generalized transport equations for the description of diffusion, sorption, radiative processes and chemical reactions are obtained taking into account the electromagnetic processes.